The great rebellion of Túpac Amaru II and the early independence of Peru: coincidences, connections, contrasts - O’Phelan Godoy, Scarlett (2021)
The article analyzes the possible connections between the Tupac Amaru rebellion and the early process of independence in Peru, trying to clarify their coincidences and contrasts. The issue is approached from comparing the conjunctures of both events, the political programs that they raised, the social composition of both moments in terms of the leadership and the bases, the participation of the clergy and, finally, making a reflection from the maturation of the independence process during the Liberal Triennium and the arrival of San Martín and Bolívar.